Synthesis and Biological Evaluation of N-3-Alkyl-Thienopyrimidin-4-Ones as mGluR1 Antagonists - Kim, Minjoo; Kim, Youngjae; Seo, Seon Hee; Baek, Du-Jong; Min, Sun-Joon; Keum, Gyochang; Choo, Hyunah (WILEY-V C H VERLAG GMBH, 2015)
Metabotropic glutamate receptor subtype 1 (mGluR1) is a potential target for the treatment of neuropathic pain, and there has been much effort to discover mGluR1 antagonists. In this study, a series of N-3-alkyl-thienopyrimidin-4-ones were prepared by introducing various alkyl and aryl groups to the N-3- and 7-positions of the thienopyrimidin-4-one core structure, respectively, and their inhibitory activities against mGluR1 were biologically evaluated. Structure-activity relationship study revealed that the trans-4-methylcyclohexyl, cycloheptyl, and cyclooctyl groups at N-3-position, and 2-fluorophenyl group at 7-position were most effective in potentiating the inhibitory activity of the thienopyrimidin-4-one derivatives against mGluR1. Among the synthesized compounds, 3-cyclooctyl-7-phenylthienopyrimidin-4-one and 3-cycloheptyl-7-(2-fluorophenyl)thienopyrimidin-4-one exhibited the most potent inhibitory activities with IC50 values of 115 and 107 nM, respectively.
Keywords: METABOTROPIC GLUTAMATE RECEPTORS; PROTEIN-COUPLED RECEPTORS; RAT-BRAIN; GROUP-I; PAIN; PHARMACOLOGY; EXPRESSION; KNOCKDOWN; BEHAVIOR; DISEASE